Astral Iconography and the Byzantine Study of the Heavens - Costache, Doru (De Medio Aevo, 2024)
Byzantine astral iconography developed from early Christian and ancient visual culture, with the latter undergoing a profound process of “Christianisation.” In turn, the early Christian fascination with stellar imagery went through stages of transformation prompted by various factors. Among these, the influence of neighbouring cultures and the widespread interest in astrology are solidly researched. But recent studies of Byzantine science, including astronomy and astrology, open new avenues of interpretation regarding astral iconography. Accordingly, this article considers the flourishing of astral iconography in Byzantium’s later centuries and in the post-Byzantine era as an outcome of scientific progress. Even so, a fuller understanding of the relevant iconography is impossible without the generous theological worldview of the Byzantines, which also legitimised the rebirth of the astral sciences.